Creating an algorithm to solve a two-step equation involves outlining a series of logical steps to isolate the variable. Here’s a simple algorithm to solve a two-step equation of the form:
\[ ax + b = c \]
where \( a \), \( b \), and \( c \) are constants, and \( x \) is the variable to solve for.
Algorithm to Solve a Two-Step Equation
Input: Coefficients \( a \), \( b \), and constant \( c \) from equation \( ax + b = c \).
Output: Value of \( x \).
Steps:
- Start
- Input the constants \( a \), \( b \), and \( c \).
- Subtract \( b \) from both sides of the equation: \[ ax + b - b = c - b \quad \text{(results in } ax = c - b\text{)} \]
- Calculate \( d = c - b \).
- Divide both sides by \( a \): \[ x = \frac{d}{a} \quad \text{(results in } x = \frac{c - b}{a}\text{)} \]
- Output the value of \( x \).
- End
Example
Let's say you want to solve the equation \( 3x + 5 = 11 \).
- Start
- Input: \( a = 3 \), \( b = 5 \), \( c = 11 \)
- Subtract \( b \): \[ 3x = 11 - 5 = 6 \]
- Calculate \( d = 11 - 5 = 6 \).
- Divide by \( a \): \[ x = \frac{6}{3} = 2 \]
- Output: \( x = 2 \)
- End
You can implement this algorithm programmatically or manually to solve any two-step equation of the specified form.